1993
DOI: 10.2166/wst.1993.0232
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Backwashing of Filters with Air Scour: A Review

Abstract: The problems occurring in the filtration facilities of water treatment plants, such as mudballs and poor initial filtrate quality are associated with the effectiveness of backwashing. Backwashing with water alone to fluidize the media is an inherently weak cleaning process. The effectiveness of backwashing is significantly improved by the use of air scour simultaneously with subfluidization water wash. When air and subfluidization water flowed concurrently through porous media, a condition termed “collapse- pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 0 publications
3
17
0
Order By: Relevance
“…During the initial saturation, entrapped air is accumulated in the dead-end and smaller pores. When the percolation begins, under the influence of capillary forces, water is absorbed into the smaller pores, and entrapped air is displaced into the larger pores, in which air cavities [Amirtharajah, 1993] are most likely created and block the pores. As a result, entrapped air blocks the largest pores, so their contribution to the water flux is diminished.…”
Section: Temporal Behavior Of Hydraulic Conductivity During Percolationsupporting
confidence: 86%
“…During the initial saturation, entrapped air is accumulated in the dead-end and smaller pores. When the percolation begins, under the influence of capillary forces, water is absorbed into the smaller pores, and entrapped air is displaced into the larger pores, in which air cavities [Amirtharajah, 1993] are most likely created and block the pores. As a result, entrapped air blocks the largest pores, so their contribution to the water flux is diminished.…”
Section: Temporal Behavior Of Hydraulic Conductivity During Percolationsupporting
confidence: 86%
“…For n on biological filters, backwash in g with water alon e h as been sh own to be an in h eren tly in effective process becau se of th e lim ited collision s an d abrasion s am on g flu idized particles. 82 More recen t research on n on biological filters h as establish ed th at th e best rem oval of particles du rin g backwash in g is ach ieved by sim u ltan eou s u se of air an d water at su bflu idization velocities to ach ieve collapse pu lsin g con dition s. 83,84 Ah m ad an d Am irth arajah 85 in vestigated th e stren gth of attach m en t of differen t particles in lab-scale biofil-ters by in clu din g h ydroph obic an d h ydration forces ( Table 2). Th eir data in dicated th at biological particles (m easu red as h eterotroph ic plate cou n ts an d cellu lar aden osin e triph osph ate) are h eld with greater force th an n on biological particles (m easu red as tu rbidity).…”
Section: Filter Mediamentioning
confidence: 99%
“…The use of appropriate backwashing strategies to ensure long‐term performance of biofilters has been emphasized in several reviews and investigations of biological filtration processes (Bablon et al, 1988; Bouwer & Crowe, 1988; Camper et al, 1987; Graese et al, 1987). In nonbiological filters, processes such as air scour improve cleaning efficacy by increasing media collisions and abrasion (Amirtharajah, 1993). The simultaneous use of air and water at subfluidization velocities to achieve collapse‐pulsing conditions has been reported as an optimal backwashing protocol for nonbiological filters (Amirthara‐jah et al, 1991) and has not demonstrated adverse effects on assimilable organic carbon removal by biological filters (Ahmad et al, 1998).…”
mentioning
confidence: 99%